Lipid extraction from Greenland halibut (Reinhardtius hippoglossoides) by-product in low-voltage DC electric field and its mechanism. (10th February 2021) - Sui, Yiming; Huang, Wen-Can; Wu, Yufan; Qi, Xiangming; Mao, Xiangzhao
Abstract: In this paper, the feasibility of extracting lipids from Greenland halibut ( Reinhardtius hippoglossoides ) by-product by low-voltage direct-current electric field was explored, and the mechanism of this method was further illustrated. By adding an appropriate amount of NaCl, an extraction rate of 80.6% ± 1.9% (1.0 g NaCl/100 g, 3 V/cm) was obtained in the experiment. Tracking of the current intensity and pH during the process indicated that cell disruption and separation of lipids in the system may be related to the movement of charged particles under the electric field. Through observation by Optical Microscope, Scanning Electron Microscope and Confocal Laser Scanning Microscope, it was more directly verified that the low-voltage direct-current electric field had a destructive effect on cell structure and lipid droplet aggregation. This research confirmed the feasibility of the use of a low-voltage direct-current electric field in lipid extraction of certain raw animal materials, and provided a basis for wider application of this technology. Graphical abstract: Image 1 Highlights: Lipid of Greenland halibut by-product was extracted in low-voltage DC electric field. Cell membrane breaking in the field was verified and its mechanism was explored. Lipids extraction rate reached 80.6% ± 1.9% at 3 V/cm with 1 g NaCl/100 g.